2014
DOI: 10.3892/mmr.2014.1929
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-34a/c function as tumor suppressors in Hep-2 laryngeal carcinoma cells and may reduce GALNT7 expression

Abstract: A family of small non-coding RNAs, ~22 nt in length, known as microRNAs (miRNAs), regulating ~30% of all human gene expression, have been reported to be involved in the pathogenesis of a number of types of cancers, including laryngeal squamous cell carcinoma (LSCC). In the current study, miR-34a and miR-34c were observed to be downregulated in human LSCC tissues. Ectopic expression of miR-34a and miR-34c in Hep-2 cells significantly induced the cell proliferation and migration ability in vitro. UDP-N-acetyl-α-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 32 publications
3
49
0
Order By: Relevance
“…Recent studies in cancer research have revealed that hsa-miR-34c is downregulated in human laryngeal squamous cell carcinoma tissues, and ectopic expression of miR-34a/c significantly induces the proliferative and migratory capacities of Hep-2 cells, in vitro (2). The imbalance between cell proliferation and apoptosis is a phenotypic characteristic of cancer, which is largely accountable for the pathogenesis of this disease.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent studies in cancer research have revealed that hsa-miR-34c is downregulated in human laryngeal squamous cell carcinoma tissues, and ectopic expression of miR-34a/c significantly induces the proliferative and migratory capacities of Hep-2 cells, in vitro (2). The imbalance between cell proliferation and apoptosis is a phenotypic characteristic of cancer, which is largely accountable for the pathogenesis of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, numerous miRNAs and genes have been verified to associate with and play crucial roles in regulating biological processes, including pathopoiesis and tumorigenesis (2,18,19). The target genes of these miRNAs, namely miR-34c (2), miR-196a (7), miR-221 (8), miR-203 (20), miR-27a (21) and miR-106b (22) have been reported to be associated with laryngeal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations